npj Science of Learning - Atteveldt, Nienke; Sah, Pankaj; Atteveldt, Nienke; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Science of Learning considers research covering all aspects of the genetic, cellular, and molecular basis of learning and memory, and understanding how children and adults learn through experience and formal educational practices. The journal covers a broad range of topics including but not limited to: Cellular and molecular studies of learning Memory formation and consolidation Memory storage and recall Cognitive neuroscience of learning Educational neuroscience Educational psychology and learning theories Learning analytics and educational data mining Technology-enhanced learning Adaptive learning systems and personalized learning platforms Metacognition and self-regulated learning Learning across the lifespan Behavioral genetics related to learning and education Social and cultural aspects of learning Assessment and evaluation in learning Transfer of learning and generalization Educational Interventions and instructional strategiess The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by learning experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Life sciences; Neurosciences; Educational technology; Neurophysiology; 9; Life Sciences; Neuroscience; Digital Education and Educational Technology; Neurophysiology; Mathematical Models of Cognitive Processes and Neural Networks